2018
DOI: 10.1007/s00586-018-5695-9
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar lordosis does not correlate with pelvic incidence in the cases with the lordosis apex located at L3 or above

Abstract: Contrary to the hypothesis, the correlation coefficient between PI and LL was not significant in the cases with apex above L3, suggesting that the relationship between PI and LL is not always constant, and whole sagittal alignment should be taken into account. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…However, the data concerning the number of patients with large PIs is small may be a characteristic of Korean elderly patients. Recent study showed similar results [38]. Finally, included people in this study were the current elderly patients in Korea and the fit BMI was a characteristic of the patients.…”
Section: Agesupporting
confidence: 68%
“…However, the data concerning the number of patients with large PIs is small may be a characteristic of Korean elderly patients. Recent study showed similar results [38]. Finally, included people in this study were the current elderly patients in Korea and the fit BMI was a characteristic of the patients.…”
Section: Agesupporting
confidence: 68%
“…In fact, in our study, the balanced group maintained optimal alignment until the last follow-up, with an average postoperative LDI of 39.5%, which is much lower than the ideal LDI of 50–80% according to the GAP score. Further, the postoperative apex was at the L2–L3 level, which is relatively more proximal compared to that in other studies [ 31 , 32 ]. Patients with LDK have a large PI [ 40 ], and the mean PI of the patients in our study was 55°.…”
Section: Discussionmentioning
confidence: 87%
“…We measured SVA, thoracic kyphosis angle (TK; T4–T10), LL angle (L1–S1), lower LL angle (LS; L4–S1), PI, PT, and sacral slope (SS) at the period of preoperative, postoperative, and at the last follow-up [ 29 , 30 ]. In order to evaluate the postoperative lordosis morphology, we measured the postoperative lordosis apex level (Apex) [ 31 ]. We measured the postoperative upper lordosis arc angle (UA) and lower lordosis arc angle (LA = SS) by dividing LL by the reference of the horizontal axis.…”
Section: Methodsmentioning
confidence: 99%
“…A number of distance and angular parameters were all measured twice by the same trained spine surgeon, and the average value was used as the final result. First, the location of the LLA, defined as the most anterior lumbar vertebra or disc in the sagittal plane [9], was measured. Vertebrae from L1 to L5 were assigned numbers ranging from 1 to 5 to simplify data collection as well as to facilitate correlation analysis.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…PI has a direct effect on the lumbar curvature of a specific individual [3,8]. Several data sets have been reported, suggesting there is a strong correlation between lumbar lordosis (LL) and PI in both normal and pathologic situations [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%